In Vitro Assessment of the Antioxidant and Antitumor Potentials of Biogenic Silver Nanoparticle - Al-basheer, A. H.; Al-wandawi , S. A. (Iraqi Journal of Science, 2020)
Silver nanoparticles (AgNPs) were biosynthesized using the cell free supernatant of putative probiotic Lactobacillus paracasei A26. Several biological activities of biogenic AgNPs were investigated in respect to in vitro anti-oxidant and anti-tumor potentials. Anti-oxidant potentials were screened in terms of free radical scavenging activity against two free radicals, 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) and resazurin dye. AgNPs exhibited a potent scavenging activity against resazurin dye (91±0.046%) with an EC50 concentration of 146.823 µg/ml, while scavenging of DPPH was significantly (P≤0.05) reduced to 72.330±0.114% using a higher EC50 concentration of 176.12 µg/ml. The anti-tumor potentials of biogenic AgNPs were studied in relation to the cytotoxicity against two human breast cancer cell lines (CAL-51 and MCF7), using crystal violet dye assay. The viability of AgNPs-treated cancerous cells was significantly decreased in a time- and concentration manner, as compared to insignificant cytotoxic effects against the normal cell line. However, the anti-proliferative activity of AgNPs did not exceed the value of 63.85±0.019% in both cancer cell lines. CAL-51 cells were the most sensitive to the introduced AgNPs, with a maximum decrease in viability of 49.889±0.021% being reached using an IC50 value of 98.65µg/ml for 48h exposure time. The inhibition percentage was increased to 60.13±0.005% when the used IC50 value was significantly declined to 40.73µg/ml with an exposure time expanded to 72h. MCF7 cells showed lower sensitivity than CAL-51 cells, but with a similar inhibition trend of 59.523±0.01% with an IC50 concentration of 66.54 µg/ml for 48h which was increased to 63.857±0.019% when the IC50 was reduced to 62.63 µg/ml and the exposure time expanded to 72h. The morphological changes of AgNPs-treated cells were apparent at 72h exposure time, with cells showing apoptotic-like features such as shrinkage and losing of regular fusiform shape. Moreover, cells became detached to surfaces and from each other.